1978
DOI: 10.1042/bj1750565
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the viscosity of mucin by serum albumin

Abstract: The interaction of serum albumin with a model epithelial mucin from pig stomach was explored by rotary viscometry. During 30 min of incubation of human serum albumin(20mg/ml) and pig gastric mucin (8mg/ml) in iso-osmotic buffers at 37 degrees C, the solution became markedly viscous. Viscosity enhancement was proportional to albumin concentration (2-40mg/ml), was most pronounced under conditions of low shear rate (less than 45S-1), and was considerably greater than the additive or multiplicative viscosity value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 47 publications
1
43
1
Order By: Relevance
“…To investigate this possibility, we added human serum albumin (the most abundant protein in plasma [25]) to healthy sputum and measured elastic and viscous moduli over 24 hours. Albumin increased the elastic and viscous moduli immediately after addition to sputum (data not shown), a finding noted previously by others (26,27). However, albumin also prevented the usual declines in mucin cross-linking and length measured over 24 hours at 378C ( Figure 4D).…”
Section: Albumin Inhibits Protease-driven Mucus Degradationsupporting
confidence: 64%
See 1 more Smart Citation
“…To investigate this possibility, we added human serum albumin (the most abundant protein in plasma [25]) to healthy sputum and measured elastic and viscous moduli over 24 hours. Albumin increased the elastic and viscous moduli immediately after addition to sputum (data not shown), a finding noted previously by others (26,27). However, albumin also prevented the usual declines in mucin cross-linking and length measured over 24 hours at 378C ( Figure 4D).…”
Section: Albumin Inhibits Protease-driven Mucus Degradationsupporting
confidence: 64%
“…We hypothesized that protease-driven digestion of mucus is inhibited by plasma proteins, which are at increased concentrations in airway mucus during acute asthma exacerbation (6,31). Albumin comprises at least 60% of plasma proteins (26), and albumin concentrations are higher than normal in airway secretions in acute asthma (25). We found that albumin mixed with mucus inhibits its normal degradation and that albumin is a substrate of neutrophil elastase.…”
Section: Discussionmentioning
confidence: 99%
“…However, binding of albumin to mucin via hydrophobic interactions has been reported. 25 This may lower the concentration of 'free' albumin in the CF sputum, which can interact with the lipoplexes.…”
Section: Does the Behavior Of Lipoplexes In The Presence Of Individuamentioning
confidence: 99%
“…A reconstituted porcine gastric mucus solution was prepared using a modification of the method reported by List et al 14 The use of lyophilized porcine gastric mucin was preferred in these studies because of the need for a matrix that contained limited nonglycoprotein contaminants that could contribute to the variability in the rheological properties of the final mucus gel. Lyophilized porcine gastric mucin Type II (40 mg/mL) was suspended in isotonic phosphate buffer (pH 6.6, the pH of mucus at the apical cell surface 15 ) containing 0.02% wt/vol sodium azide and stirred overnight at 4-C.…”
Section: Reconstitution and Purification Of Mucusmentioning
confidence: 99%